Proposta metodológica de cálculo para a pegada hídrica na construção civil imobiliária - Souza, Jackeline Lucas (2016)
This paper aims to propose a calculation methodolog y to measure the water footprint (PH) in the real estate construction activity. The water fo otprint is an empirical quantity indicator, the period and the place where the water is consumed an d polluted, which is measured over the entire productive chain of a product showing not on ly the volume of water, as well as the type of water use (consumptive, rain, surface or undergr ound, or water pollution), the location and the time when water was used. To calculate the wate r footprint in housing construction activity was used the methodology of Hoekstra et al. (2011) using the partial concept of 'blue water' - a kind of measure of ownership of the water footprint determined by consumption, evaporation and runoff into the ocean - in its use / consumptio n for human purposes in order to estimate the quantum of water is required to produce a residenti al building. The measurement was divided into three groups that make up civil construction a ctivity, namely: labor, materials and services. The results showed statistically that a sample of 9 0 workers could be extrapolated to the average of workers employed throughout the work (115 employ ees), allowing to measure the volume of water consumption (water footprint) for the grou p of hand work was 1124068200.0 l of water (distributed direct and indirect) for the materials group consisting of 128 items that have water component, the water footprint was 30,100,539.5 l o f water (Indirect) and for the service group, consisting of 92 items that use water, the water fo otprint was 584,427,948.4 l of water (Direct), ie the total of the enterprise the water footprint of 1738596688.0 l . The most relevant consumption workmanship were given to the categorie s 'liquid' and 'other higienes' in PH Direct and 'industrialized' and 'transport' in PH Indirect ; for the most outstanding materials was evidenced in 'irons CA' (PH Indirect), and in servi ces, the largest water consumption was evident in the service of 'mechanical protection' ( PH Direct). The total amount of water consumption (1738596688.0 l) divided by the total a rea of the project (in m 2 ) resulted in 93978.2 l / m 2 , where the housing unit of 157.14 m 2 has a water footprint of 14,767. 734.2 l and 167.12 m 2 one water footprint of 15705636.8 l. It follows th at the water footprint is a calculation method capable of measuring the volume of water con sumed in construction activity, allowing builders estimate this volume from the work plannin g stage in order to manage this scarce environmental resource.